Endonasal endoscopic resection of suprasellar craniopharyngioma: A retrospective single-center case series. (November 2020) - Simonin, Alexandre; Bangash, Omar; Henley, David; Bala, Arul
Highlights: Endonasal endoscopic approach is a safe and effective surgical option. Gross total resection can be achieved in most of the cases. Endonasal endoscopic approach can also be used for recurrences. Abstract: Introduction: Endoscopic endonasal approach (EEA) has recently been proposed as an option for resection of primary and recurrent suprasellar craniopharyngioma. However, surgical outcome has not yet been fully evaluated, especially in regards to recurrent cases. Methods: We analysed our institution (Sir Charles Gairdner University Hospital, Perth, Australia) case-series retrospectively. There were 16 patients operated through an endonasal endoscopic approach from February 2014 to February 2019 for suprasellar craniopharyngiomas. There were 14 primary, and two recurrent lesions. Extent of resection, complications, visual and endocrinological outcomes are presented. Results: Mean age of the patients was 42.9 ± 19.3 years old, with 56% female. The most common clinical symptoms were headaches (9 patients, 56%) and bi-temporal hemianopsia (9 patients, 56%), followed by unilateral optic neuropathy (5 cases, 31%), memory loss (1 case, 6%), hydrocephalus (1 case, 6%), delayed growth and puberty (1 case, 6%), and secondary amenorrhoea (1 case, 6%). Only two cases (12%) initially presented with normal visual function. Gross total resection (GTR) was achieved in 10/16 patients (62.5%), with subtotal resection (STR) in the remainder. Visual symptoms improved in 13/16 patients (81%) and remained unchanged in 3/16 patients (19%). Most common complications included new endocrinological deficit in nine patients (56%), mostly diabetes insipidus, and cerebrospinal fluid leak requiring a new intervention in three patients (19%). There was one mortality case (complicated meningitis, stroke and vasospasm). Mean follow-up time was 22.05 ± 14 months and three patients (19%) had a recurrence of the disease during this period and were referred for radiation therapy. Conclusion: Endonasal endoscopic approach is a safe and effective surgical option for both primary and recurrent suprasellar craniopharyngiomas.